Soil, Plant Species and Encroachment Status of Sal Forest in Bangladesh - Mondol , M. A.; Wadud , M. A.; Rahman, G. M. M. (European Journal of Applied Sciences, 2021)
The study investigated the soil fertility status of denuded encroached forest and naturally vegetation covered forest area, plant species diversity and structural composition, encroachment status of BNP and MNP ranges of Sal forest. Soil fertility status was measured before (March to April) and after (September to October) the monsoon. Soil samples were collected before monsoon (March to April) and after monsoon (September to October) from Sal tree covered areas and from deforested areas only after the monsoon. In all situations soil samples were collected from 0-15 cm and 16-30 cm depth. Physico-chemical characters such as soil texture, colour, pH, organic matter (%), nitrogen (%), phosphorus (ppm), potassium (meq./100g) and sulphur (ppm) were estimated. The study revealed that physico-chemical characteristics of Bhawal and Madhupur Sal forest areas were almost similar but the soil of upper layer (0-15cm depth) was more fertile than deeper soil (16-30cm depth). The physico-chemical characteristics of soil of denuded and encroached areas of both Bhawal and Madhupur forests were severely declined compared to Sal tree covered areas soil. All physico-chemical characteristics (soil texture, colour, pH, organic matter, nitrogen, phosphorus, potassium and sulphur) of denuded and encroached areas soil were low in both the forests compared to naturally sal tree covered areas in both the situations i. e., surface (0-15cm depth) and sub surface (16-30cm depth) soil. For estimating the plant species diversity and structural composition, ‘Count Quadrats or list-count quadrats’ method was used. Total 80 quadrats (10 m x 10 m) were surveyed of which 30 from BNP range and 50 from MNP range for collecting plants species information. In the BNP range, total 49 plant species were identified of which 24 trees, 4 shrubs, 7 climbers and 14 herbs species. These 49 plants species of this Sal forest belong to 30 families and 43 genera. In the MNP range of Sal forest area, total 112 plant species were identified of which 60 trees, 9 shrubs, 19 climbers and 23 herbs species. These 112 plant species of Madhupur Sal forest belong to 50 families and 93 genera. Structural composition were evaluated with regard to their density, relative density, frequency, relative frequency, abundance, dominance, relative dominance of a species, total basal coverage, importance value index (IVI), diversity index and beta diversity. Total 47 plant species were similar between this BNP and MNP range of Sal forest and beta diversity index was 0.584. Considering all above indices it was found in both the Sal forests that community species diversity and plant population density were very low. IVI value of plant community in the BNP range of Sal forest ranged from 121.584 to 0.596. Based on IVI value Shorea robusta (121.584), Ageratum conyzoiodes (23.02), Clerodendrum squamatum (19.87), Randia dumetorum (13.74), Aphanamixis polystachaya (11.87), Glycosmis pentaphyla (11.03), Butea monosperma (7.29) and Phyllanthus emblica (5.75) were the dominant species in this Sal forest. Five species possess the IVI value less than one, indicating these are in endangered condition. IVI of plant community in the Madhupur Sal forest area ranged from 93.336 to 0.246. Based on IVI value Shorea robusta (93.34), Ageratum conyzoiodes (32.31), Mallotus philippensis (21.45), Clerodendrum squamatum (17.53), Randia dumetorum (16.19), Aphanamixis polystachaya (13.18), Glycosmis pentaphyla (11.93), Calotropus procera (9.13), Phyllanthus reticulatus (7.78), Dillenia pentagyna (6.01) and Paederia foetida (4.36) were the most dominant plant species in this forest. More than 14 species possess the IVI value less than 0.5, indicating these are in endangered condition. According to the opinion of the local people, Sal forest is severely degraded, deforested and encroached. They opined only 16.09 and 19.37% area of BNP and MNP ranges of Sal forest is vegetation covered and rest part is encroached. Respondents are also noticed the species diversity also severely reduced in Bhawal and Madhupur Sal forest. Fourteen causes are identified which are responsible for encroachment and deforestation of which setting up of industries, monoculture of exotic tree species, cash crops cultivation, illegal felling of tree, ill motive of forest authority as well as local people are mentionable. Total 12 options were suggested for protecting Sal forest by the respondents of Bhawal and Madhupur. They essentially mentioned patriotism of local people, honesty of forest department authority, and consciousness of Government can only save the Sal forest as well as maintain an ecological balanced condition in Bangladesh.